Food for thought: Family Entrepreneurship in four questions - Kathleen Randerson (Boletín de Estudios Económicos)
Family Entrepreneurship is a growing field of study. The purpose of this essay is to relay the momentum to academics, practitioners, and society. The essay is structured around four thought provoking questions: who is family?, what role do values play?, what is entrepreneurship?, and why is the business family and family business situation so complicated? These questions and the elements of response offered lead to a wider and deeper understanding of Family Entrepreneurship at the individual, family, and family business levels. Contributions to theory are twofold. First this essay underscores the need for a contextualized understanding and action and provides frameworks to undertake them. Second, it sheds light on the damages incurred by focussing on mainstream and generalizations by teasing out important aspects until now ignored. Contributions to practice concern a wider and deeper understanding of Family Entrepreneurship, recognizing and supporting situationally adapted behaviors as entrepreneurial, and widening the identified outcomes of these behaviors. Contributions to society are linked to the prevalence of business families and family businesses in economies and societies worldwide. Using this weight for societal impact, Family Entrepreneurship can be a beacon for transition towards economies and societies that are more collaborative, just, and sober.